Pengaruh Motif Dan Kesiapan Terhadap Hasil Belajar Pengantar Akuntansi 1 - Rima Kurnia; Sany Dwita; Salma Taqwa (Universitas Negeri Padang, 2019)
This study aims to test empirically about: 1) The influence of motives on learning outcomes introductory accounting 1, 2) the influence of readiness for learning outcomes introductory accounting 1. This type of research is causative. Data in the study were collected using a questionnaire on 185 accounting students from an university in Padang City. Data analysis was performed using multiple regression analysis. The results of this study conclude that the motive influences the learning outcomes of one person's accounting introduction and the readiness to influence one's accounting learning outcomes. This research focuses on the importance of introductory accounting learning outcomes 1 because the subject is a basic course that will be useful for the next course and make accounting students of class 2014, 2015 and 2017 as the population